Digitalization of HYPOGLYRISK and Evaluation of Its Utility for Pharmacist-Led Hypoglycemia Risk Assessment in Type 2 Diabetes Mellitus - Made Krisna Adi Jaya; Zullies Ikawati; Fita Rahmawati; Nanang Munif Yasin; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Ilmiah Medicamento, 2026)
Background: We developed a tool for pharmacists to facilitate screening of medication-related hypoglycemia risk in patients with type 2 diabetes mellitus (T2DM), called HYPOGLYRISK. Although this instrument has been validated and proven reliable, the paper-based version was considered inefficient and prone to human error during routine screening.Objective: This study aimed to digitalize HYPOGLYRISK and evaluate its utility compared with the printed version.Methods: A mixed-method study design combining software development and a quasi-experimental trial was used. In the development stage, the application was created using Android Studio and validated through Black Box Testing and User Acceptance Testing (UAT). In the trial stage, 46 pharmacists participated and were divided into two groups using either the digital or paper-based HYPOGLYRISK to assess simulated ambulatory T2DM patients representing different hypoglycemia risk categories. The primary outcome was assessment time efficiency, while the secondary outcome was the potential for human error. Data were analyzed using the Mann-Whitney U test, chi-square test, and relative risk analysis.Results: The digital HYPOGLYRISK demonstrated significantly shorter assessment time compared with the conventional version (p<0.05) and reduced the probability of scoring errors by 3.3 times (p<0.05). The digital application also provided additional advantages, including efficiency, scalability, ease of use, rapid data access, and simplified data management.Conclusion: These findings suggest that digital HYPOGLYRISK can enhance pharmacist-led hypoglycemia risk assessment among ambulatory patients with T2DM.